2017
DOI: 10.20319/lijhls.2017.32.6576
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation to Adaptation of Motherhood in Postpartum Period

Abstract: The purpose of this study was to examine women ' 22.19±4.17 (min:18-max:44) and average length of marriage is 6. 21±5.48 (min:1-max:25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…According to the results from the studies, quality of life in women was moderate at 6 -8 and 12 -14 weeks postpartum (24,27). Therefore, the protective measures by the spouse, family members, and caregivers during pregnancy and post-partum are necessary to improve the quality of life and health status of the mothers (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results from the studies, quality of life in women was moderate at 6 -8 and 12 -14 weeks postpartum (24,27). Therefore, the protective measures by the spouse, family members, and caregivers during pregnancy and post-partum are necessary to improve the quality of life and health status of the mothers (27).…”
Section: Discussionmentioning
confidence: 99%
“…It can be said that vulnerability in women during this period is associated with reduced selfcare during post-partum (1). The midwife is considered to play a significant role in post-partum transition (24), counseling and maternal care during pregnancy, childbirth, and post-partum (25), maintaining and improving maternal and infant health, providing favorable care, counseling, and teaching health to women, family and society (26). Therefore, the midwife should assess the women in terms of their risk factors, mental and physical health, and compatibility with post-partum conditions, and educate the appropriate preventative strategies and provide the necessary care (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with good adaptation to the maternal role during pregnancy are more likely to rely on power in coping with postpartum maternal duties 3,17 . Factors, such as education level, occupation, income level, and social security, which determine the sociological status of women, are very significant factors affecting the maternal role of women 18 . In this study, it was found that the score obtained from the subscale relying on power in coping with maternal duties did not change according to the age, education time, employment, and economic status of the women.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that the score obtained from the subscale relying on power in coping with maternal duties did not change according to the age, education time, employment, and economic status of the women. In the studies, it was determined that mothers, who had high income 5,18 and education levels, who were at an advanced age, and who worked 5,18 , had better adaptation to the maternal role. In order to facilitate adaptation to the process of transition to maternity, it is vital that health care providers know this process.…”
Section: Discussionmentioning
confidence: 99%